Relação da concentração do hormônio antimulleriano com população folicular e fertilidade em fêmeas bovinas - Pupulim, Antônio Guilherme Roncada [UNESP] (2013)
In bovines follicular development happens in a wave pattern that can vary from two to three waves per estral cycle with a group of follicles growing simultaneously but with only ano becoming the dominat follicle. The number of recruited follicle is highly variable between animal; however it is highly repeatable within an animal. Bos indicus animals present greater number of follicles per wave than Bos taurus animals. The objective of the present study was 1) identify animals from the Nelore and Abeerden Angus breed that have high or low number of follicles recruited per follicle wave and relate the number of follicles with AMH concentration; 2) to relate the number of antral follicles with the fertility of Nelore females; 3) to determine if the superstimulatory treatment alters the plasmatic concentrations of AMH. In experiment 1 the follicle count in Nelore and Angus heifers was done through two ultrasound examinations (US). Considering the mean + SEM of the follicle count in each breed, the heifers were grouped in high (HFC) or low (LFC) follicle count. Plasmatic AMH was measured in a blood smple drawn at the last US. In Experiment 2, there were used Nelore heifers submitted to a TFAI protocol. Heifers were grouped in HFC (>40 follicles), intermediary (>20 an <40 follicle) and LFC (<20 follicle). In experiment 3, Nelore cows with high and intermediary follicles counts were used. Animals were separated in control TFAI group and P36 group. Blood samples for AMH measurement were collected on day 5 (P36) and on day 8 (TFAI and P36). Result from experiment 1 were analyzed using ANOVA. Experiment 2 was analyzed using a logistic regression and experiment 3 was ...